An Application Of Integrated Marketing Communications In Wyeth(M) Sdn Bhd - Cheam, Yean Joo (2008)
Integrated marketing communication has been popularly used as a strategic management process to create and manage strong brands effectively. The marketing communication tools and strategies used in Wyeth (M) Sdn Bhd have been broadly researched. This case study is conducted through data and information collected from many sources of evidence.